2012
DOI: 10.1016/j.seizure.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of folic acid depletion on homocysteine serum level in children and adolescents with epilepsy and different MTHFR C677T genotypes

Abstract: Homocysteine (Hcy) is a sulfur-containing amino acid involved in methionine metabolism. An elevated total plasma Hcy concentration (tHcy) is a risk factor for vascular disease. The present study aimed to assess the role of antiepileptic drugs (AEDs) and C677T methylenetetrahydrofolate (MTHFR) polymorphisms on tHcy in pediatric patients with epilepsy treated for at least 6 months with various treatment regimens protocols including the newer AEDs. The study group was recruited from children and adolescents with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Hence, in our study, the cut-off for defining hyperhomocysteinaemia was taken as >10.4 μmol/L, as previously suggested by Coppola et al and Huemer et al 3 11. Because of the lower cut-offs used to define hyperhomocysteinaemia in our study, 34% of control children also had raised Hcy concentrations.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Hence, in our study, the cut-off for defining hyperhomocysteinaemia was taken as >10.4 μmol/L, as previously suggested by Coppola et al and Huemer et al 3 11. Because of the lower cut-offs used to define hyperhomocysteinaemia in our study, 34% of control children also had raised Hcy concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…An inverse relationship exists between the amount of Hcy present in the patient sample and the amount of relative light units (RLUs) detected by the system. A total Hcy value of ≥10.4 µmol/L was considered as hyperhomocysteinaemia in the children 3 11 19 20…”
Section: Methodsmentioning
confidence: 99%
“…[820] The tHcy level exceeded the 90 th age percentile in 13.8% Japanese and 40.4% of Spanish children taking AEDs. [2122] A prospective study reported that 5 μmol/l higher tHcy level was associated with a 27% higher risk for venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…[8914] Considering the biological plausibility, many doctors are now prescribing folic acid to those undergoing treatment with AEDs, though there is a paucity of data from India. In this context, the present study was conducted with the following objectives: (1) to assess the level of tHcy in children taking AEDs and (2) to study whether daily oral supplementation of folic acid will reduce the tHcy level in them.…”
Section: Introductionmentioning
confidence: 99%
“…t‐Hcy levels were determined via fluorescence polarization immunoassay. The serum folate concentration was determined using commercial kits (ACS180 PLUS: Ciba‐Corning, Tianjin, China; and Immulite: Diagnostic Products Corporation, Tianjin, China) as described in detail by Coppola et al 21 …”
Section: Methodsmentioning
confidence: 99%